Speed vs completeness: a comparative study of solitary and colonial tunicate embryogenesis - Anselmi, Chiara; Ishizuka, Katherine J.; Palmeri, Karla J.; Burighel, Paolo; Voskoboynik, Ayelet; Hotta, Kohji; Manni, Lucia (Frontiers in Cell and Developmental Biology, 2025)
Solitary ascidians, such as Ciona robusta, have been used for over a century as model systems for embryological studies. These species are oviparous, producing many relatively small and transparent eggs, which are released and fertilized outside the parent body. Embryos develop rapidly in a stereotyped manner and reach the larva stage in less than 1 day (at 20°C). The larvae then settle and metamorphose into sessile juveniles in approximately 2 days. On the other hand, colonial ascidians are ovoviviparous, with heavily yolked eggs that develop inside the parent body. In the colonial Botryllus schlosseri, embryos are connected to the parental body via a cup-like placenta and develop into larvae within a week (at 20°C). These larvae, which possess both typical larval organs and prospective juvenile organs, are released into seawater, where they settle very rapidly, sometimes after only 15 minutes of free swimming. Then, they metamorphose into juvenile oozooids. The ability to study embryo development in colonial ascidians within the parent body is limited. To address this, we developed a method for in vitro culturing B. schlosseri embryos outside the parental body and combined it with time-lapse and confocal microscopy to describe the embryonic developmental stages. Moreover, we used histological analysis based on serial sections to investigate late-stage development, when embryo opacity made other techniques ineffective. We identified 19 stages of development, from the fertilized egg to the swimming larva, and described the stage of organ appearance and differentiation. Comparing the embryonic development timeline of B. schlosseri with that of C. robusta, we found heterochrony in development, particularly in the timing of organ appearance and growth rate. We hypothesize that this difference in maturation timing between solitary and colonial ascidians reflects a shift in the regulation of key developmental pathways that contributed to ascidian diversification. This heterochronic evolution likely facilitated a significant (approximately four-fold) shortening of the metamorphosis time in B. schlosseri by allowing embryos to remain in a safe ovoviviparous environment five times longer than those in C. robusta before hatching.